Pengaruh Profitabilitas, Likuiditas dan Opini Audit Terhadap Kualitas Audit dengan Kualitas Audit sebagai Variabel Pemoderasi - Ferreriano Joseph Riantio Wadhi; Budi Kurniawan (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to examine the effect of profitability, liquidity, and audit opinion on audit delay with audit quality as a moderating variable. The sample used in this study is a manufacturing company that is consistently listed on the Indonesia Stock Exchange in the 2015-2019 period, with a total sample of 63 companies using the purposive sampling method with the data analysis method using the panel data regression method. The results of this study indicate that profitability has no effect on audit delay, liquidity has no effect on audit delay, audit opinion has no effect on audit delay, audit quality is able to moderate profitability on audit delay and quality is not able to moderate liquidity and audit opinion on audit delay.